Can serum asymmetric dimethyl-arginine and homocysteine levels be a new activity parameter of disease in patients with rheumatoid arthritis? - Akgol, Gurkan; Gulkesen, Arif; Telo, Selda; Ulusoy, Hasan; Poyraz, Ahmet Kursad; Alkan, Gokhan; Kaya, Arzu (E-Century Publishing Corp, 2016)
In this study, we evaluated serum asymmetric dimethyl arginine (ADMA) level, homocysteine level and its clinical significance in rheumatoid arthritis (RA). The study included 40 patients with RA and 30 controls. Serum ADMA and homocysteine levels were measured using High Performance Liquid Chromatography system. Patients with DAS 28 scores <= 3.2, and > 3.2 were allocated into lower and high/moderate disease activity groups, respectively. Additionally patients were divided into 2 groups as early RA (disease duration <= 2 years) and established RA (duration of the disease >= 2 years). Functional disability was evaluated using Health Assessment Questionnaire (HAQ). Radiographs were scored using the modified Larsen score. Serum ADMA level was significantly higher than controls (P=0.008) in RA patients, while homocysteine level was comparable (P=0.059). Serum ADMA and homocysteine levels did not correlate with clinical and laboratory parameters of disease activity such as erythrocyte sedimentation rate, C-reactive protein, Disease Activity Score (DAS) 28 and Health Assessment Questionnaire (HAQ). These outcomes demonstrate that ADMA and homocysteine levels cannot be used as a parameter for disease activity in RA.
Keywords: Rheumatoid arthritis; asymmetric dimethyl arginine; homocysteine; disease activity